TEORI LINGUISTIK DAN PSIKOLOGI DALAM PEMBELAJARAN BAHASA - Saepudin Saepudin (Al-Ishlah: Jurnal Pendidikan Islam, 2018)
This article discusses several language theories and psychological theories thatinfluence the educator's point of view in teaching languages both mother tongueand second language learners. Among the linguistic theories described arestructuralism theories pioneered by Ferdinand de Saussure in Europe; the firstfigure to do a study of language with scientific principles and codified so that it canbe analyzed using systematic and clear methods. Other figures in this genre areLeonardo Bloomfield, Edward Saphier, Charles Hokait and Charles Fries. Second,the transformational generative theory pioneered by Noam Chomsky, who wasborn in 1928 in Pennsylvania, United States. Psychological theories discussed arethe theories of behaviorism, nativism, cognitivism, functional, constructivism,humanism and cybernetics